The regulation and function of acetylated high-mobility group box 1 during implantation and decidualization - Li, Yue; Chen, Si-Ting; He, Yu-Ying; Li, Bo; Yang, Chen; Yang, Zhen-Shan; Yang, Zeng-Ming (Frontiers in Immunology, 2023)
High-mobility group box 1 (HMGB1) is a non-histone nuclear protein and can be extracellularly secreted as damage-associated molecular pattern (DAMP) molecule to induce sterile inflammation. Although uterine deletion of HMGB1 causes implantation and decidualization defects, how secreted HMGB1 is involved in mouse early pregnancy is still unknown. In our study, the secreted HMGB1 was detected in uterine lumen fluid in mouse periimplantation uterus. There is an obvious difference for secreted HMGB1 levels in uterine fluid between day 4 of pregnancy and day 4 of pseudopregnancy, suggesting the involvement of blastocysts during HMGB1 secretion. Trypsin is clearly detected in mouse blastocyst cavity and in the supernatant of cultured blastocysts. Trypsin significantly stimulates HB-EGF production through activating PAR2 and ADAM17. Uterine injection of PAR2 inhibitor into day 4 pregnant mice significantly reduces the number of implantation sites. HB-EGF released from luminal epithelium can induce mouse in vitro decidualization. The conditioned medium collected from trypsin-treated luminal epithelium is able to induce in vitro decidualization, which is suppressed by EGFR inhibitor. Intrauterine injection of glycyrrhizin (HMGB1 inhibitor) can significantly inhibit mouse embryo implantation. We also showed that exogenous HMGB1 released from human epithelial cells are able to induce human in vitro decidualization through PAR2-ADAM17-HB-EGF pathway. Although excessive inflammation often causes infertility, a physiological level of exogenous HMGB1 should be beneficial for mouse and human decidualization. In this study, we show that trypsin can induce decidualization of stromal cells via PAR2-HMGB1-ADAM17-HB-EGF from luminal epithelium.